2022
DOI: 10.1186/s12916-022-02581-0
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of vascular risk factors underlying the link between gestational diabetes and cardiovascular disease

Abstract: Background Women with gestational diabetes (GDM) have an elevated lifetime incidence of cardiovascular disease (CVD), but the basis of this excess risk remains to be established. In this context, we hypothesized that chronic exposure to adverse cardiovascular risk factors may contribute to their elevated risk of CVD. We thus sought to quantify the determinants of CVD risk in women with a history of GDM by performing mediation analyses. Methods Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…147 Data from the Women’s Health Initiative also suggest that hypertension and BMI at the time of study enrollment mediated 24% and 20% of the association between HDP and incident heart failure, respectively. 148 Among those with a history of GDM, risk of CVD was significantly mediated by HbA1c (56%), fasting glucose (46%), HDL cholesterol (25%), and triglyceride levels (12.1%) measured at approximately 4 to 9 years post-partum. 149 Risk factor levels following an APO may signal those who are most likely to develop chronic risk factors.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 94%
“…147 Data from the Women’s Health Initiative also suggest that hypertension and BMI at the time of study enrollment mediated 24% and 20% of the association between HDP and incident heart failure, respectively. 148 Among those with a history of GDM, risk of CVD was significantly mediated by HbA1c (56%), fasting glucose (46%), HDL cholesterol (25%), and triglyceride levels (12.1%) measured at approximately 4 to 9 years post-partum. 149 Risk factor levels following an APO may signal those who are most likely to develop chronic risk factors.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 94%
“…On the other hand, Yu et al quantified the impact of type 2 diabetes after GDM using mediation analysis in a Danish nationwide cohort of 1 million parous women observed over 16 years and reported that one-fifth of the increased relative risk of CVD among women with GDM compared with those without could be explained by subsequent type 2 diabetes 8 . Retnakaran et al 6 conducted a retrospective analysis of a cohort of 0.7 million women with a live-birth pregnancy in followed for 13 years and found that the HbA1c and fasting glucose were major determinants (56 and 47%, respectively) for excess CVD risk in women with GDM compared with those without GDM. These proportion estimates were based on measures of relative risk and we supplemented these estimates by firstly reporting the proportion of absolute health burden that could be attributable to subsequent diabetes in women with GDM.…”
Section: Population Health Burden Attributable To Diabetesmentioning
confidence: 99%
“…A few studies have reported the contribution of incident diabetes or hyperglycemia to excess relative risk of cardiovascular disease (CVD), renal dialysis, and hospitalization for foot infection in women with compared with those without GDM 6 , 7 , 8 . However, the proportion in absolute terms is still unknown, specifically, the population attributable fraction (PAF), which is commonly defined as the proportion of cases that would have been prevented over a specified time interval had the exposure of interest been eliminated from the population while distributions of other risk factors in the population remain unchanged 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms linking GDM to HF are currently unclear. Women with history of GDM have greater exposure to increased glycemia and dyslipidemia independent of subsequent diabetes development [79]. This hyperglycemia may lead to myocardial fibrosis and remodeling similar to the processes related to diabetic cardiomyopathy [80].…”
Section: Gestational Diabetes and Heart Failurementioning
confidence: 99%